Comparison of Respiratory Variations of Subclavian Vein and Inferior Vena Cava in Hospitalized Patients with Kidney Disease - Kaptein EM; Cantillep A; Kaptein JS; Oo Z; Thu MB; Thwe PP; Kaptein MJ (International Journal of Nephrology and Renovascular Disease, 2020)
Elaine M Kaptein,1 Alan Cantillep,1 John S Kaptein,1 Zayar Oo,1 Myint B Thu,1 Phyu Phyu Thwe,1 Matthew J Kaptein1,2 1Department of Medicine, Division of Nephrology, University of Southern California, Los Angeles, CA, USA; 2Department of Medicine, Division of Nephrology, Loma Linda University Medical Center, Loma Linda, CA, USACorrespondence: Elaine M Kaptein Tel +1 213 220-0373Email ekaptein@usc.eduBackground: Accurate assessment of relative intravascular volume is critical for appropriate volume management of patients with kidney disease. Respiratory variations of inferior vena cava (IVC) diameter have been used and may correlate with those of subclavian vein (SCV) by bedside ultrasound. The purpose of this study was to assess the relationship between SCV and IVC respiratory variations by bedside ultrasound in a large group of hospitalized patients with acute and/or chronic kidney disease.Methods: We compared 160 paired SCV and IVC bedside ultrasound studies from 102 semi-recumbent hospitalized adult patients with kidney disease. Patient encounters in which the SCV or IVC could not be clearly visualized were excluded. Collapsibility index=(Dmax–Dmin)/Dmax*100%; D=venous diameter.Results: Relationships between SCV collapsibility index and IVC collapsibility index were not different for longitudinal and transverse views of the SCV. Correlation of SCV collapsibility index with IVC collapsibility index was 0.75 for mechanical ventilation (n=65, P< 0.0001) and 0.67 for spontaneous breathing (n=95, P< 0.0001). IVC collapsibility index cut-offs < 20% for hypervolemia and > 50% for hypovolemia corresponded to SCV collapsibility index cut-offs of < 22% and > 39%, respectively, for both mechanical ventilation and spontaneous breathing encounters. Using these cut-offs for SCV collapsibilities, assessment as hypervolemia versus not-hypervolemia had maximal sensitivity and specificity for predicting respective IVC collapsibility cut-offs of 88% for mechanical ventilation and 74% for spontaneous breathing, and assessment as hypovolemia versus not-hypovolemia had maximal sensitivity and specificity of 91% and 70%, respectively. Concordance, defined as agreement between assessment using SCV CI and assessment using IVC CI, was 85% for mechanical ventilation and 72% for spontaneous breathing when differentiating hypervolemia versus not-hypervolemia and was 89% and 71% respectively when differentiating hypovolemia versus not-hypovolemia.Conclusion: Assessment using SCV collapsibility index in the semi-recumbent position has a reasonable concordance with assessment using IVC collapsibility index for both spontaneous breathing and mechanical ventilation, in a wide range of hospitalized patients with concurrent kidney disease, and may be a useful adjunct to assess relative intravascular volume in patients with kidney disease.Keywords: acute kidney injury, chronic kidney disease, end-stage kidney disease, hospitalized patients, inferior vena cava ultrasound, intravascular volume assessment, point-of-care ultrasound, subclavian vein ultrasound, venous collapsibility index